Beyond the Basics: Examining the Consequences of Substandard Law Textbooks in Legal Education in Developing Countries - Abu Hena Mostofa Kamal; Mohd Zakhiri Md. Nor; Mohammad Abu Taher; Mohammad Abdul Matin Chowdhury (Lex Publica, 2024)
Law graduates play a critical role in shaping the legal system and ensuring justice. To provide them with the necessary knowledge and skills, it is essential to have proper educational resources, especially qualitative law textbooks. This article evaluates the need for qualitative law textbooks for proper education of law graduates in law schools by taking Bangladesh as a case study and critically assesses the impact of the lack of quality textbooks on law students. The study shows that qualitative law textbooks are essential for students to develop a comprehensive understanding of the legal system, its principles, and the interpretation of laws. Lack of quality textbooks has a detrimental impact on law students in Bangladesh, hindering their research and academic progress and affecting the quality of legal education. This article argues that it is imperative to ensure the availability of qualitative law textbooks to provide the necessary educational resources for law students in Bangladesh. The study highlights the significance of qualitative law textbooks in legal education and calls for necessary measures to address the issue of insufficient textbook quality to improve legal education in Bangladesh.